Sangkameteng Karawitan Composition | Komposisi Karawitan Sangkameteng - I Gede Edo Prasetya Dewantara; Kadek Suartaya; I Ketut Garwa (Pusat Penerbitan LPPMPP ISI Denpasar, 2021)
The purpose of making this artwork is to convey a moral message to the public about the importance of preserving a local wisdom that has developed in Desa Adat Renon (Traditional Village), Renon Village, South Denpasar through a new youthful and contemporary spirit musical artwork. The composer created stages of Sankameteng artwork inspired from the Alma M. Hawkins concept presented in his book Creating Through Dance. He stated that the creation of an artwork was taken through three stages, namely the exploration, improvisation and the forming stage. Related to the artwork media, the composer used Wesi Cwaram's gamelan as the implementation of the ideas and concepts. Gamelan Wesi Cwaram is a new gamelan ensemble that emerges after the development of the Selonding gamelan. Sankameteng karawitan artwork uses parts that are arranged according to the atmosphere to be achieved. A series of scenes from a dusk state called sandikala (nightfall) and memeteng (in the dark) as a result of ngaturang procession presented in the song structural parts, divided into three parts, namely, part I, part II, and part III. Academic artists are artists who have more abilities in their fields, especially in academic matters. As an academic artist, one should be able to contribute and be dedicated to society.